Question Paper Design in Line with Outcome-Based Education Policy - Bhandurge, Parixit; Suryawanshi, Shailendra Sanjay (Indian Journal of Pharmaceutical Education and Research, 2024)
Outcome-Based Education (OBE) is an educational framework that focuses on achieving specific, measurable outcomes in terms of student learning and performance. Unlike traditional education models that emphasize content delivery and time-based progression, OBE starts with the end goals-what students should know, are able to do and be able to demonstrate after they complete a program. These outcomes are clearly defined and serve as the foundation for curriculum design, teaching methods and assessment strategies. A question paper is an essential tool in the educational assessment process, designed to evaluate students' understanding, knowledge and skills in a specific subject area. The structure and content of a question paper are usually aligned with the learning objectives and outcomes of the course, ensuring that the assessment is both comprehensive and fair. A well-designed question paper not only measures students' mastery of the subject matter but also provides valuable feedback to educators about the effectiveness of their teaching methods. In this publication we have provided detailed process for preparing the structured question paper. The proposed publication concludes that framing a question paper in line with OBE requires careful alignment with these predefined outcomes. The process of creating test questions should be addressed systematically. It involves aligning questions with specific learning outcomes, ensuring a variety of question types and difficulty levels and providing clear instructions and fair marks allocation. This approach helps in accurately assessing students' achievement of learning outcomes and supports a more targeted and effective teaching-learning process.
Keywords: Assessment; Learning Outcomes; Outcome Based Education; Question Paper; Teaching-Learning